2023
DOI: 10.3389/fendo.2022.1049665
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity and its negative impact on female fertility and maternal pregnancy outcomes

Abstract: Thyroid autoimmunity (TAI) is commonly defined as the presence of thyroperoxidase antibodies (TPOAbs) and/or thyroglobulin antibodies (TgAbs), which predisposes an individual to hypothyroidism. TAI affects nearly 10% of women of reproductive age and evokes great interest from clinicians because of its potentially negative impact on female fertility and pregnancy course. In this mini-review, we review the current literature concerning the influence of TPOAb or TPOAb/TgAb positivity without thyroid dysfunction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…Furthermore, immune abnormalities linked with thyroid diseases, particularly thyroid autoimmunity (TAI), are connected to an elevated risk of RPL in women (43). TAI can induce immunological dysfunction and impede immune tolerance at both systemic and maternal-fetal interface levels (44). Additionally, thyroid autoantibodies, particularly TGAb, could be an expression of a more general maternal immune system abnormality leading to RPL (45).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, immune abnormalities linked with thyroid diseases, particularly thyroid autoimmunity (TAI), are connected to an elevated risk of RPL in women (43). TAI can induce immunological dysfunction and impede immune tolerance at both systemic and maternal-fetal interface levels (44). Additionally, thyroid autoantibodies, particularly TGAb, could be an expression of a more general maternal immune system abnormality leading to RPL (45).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TPO positivity is a marker of autoimmune thyroid disorders (Graves’ Disease and Hashimoto Thyroiditis) and is linked with male and female subfertility, even in subjects with biochemically normal thyroid function [ 64 , 65 ]. Thyroid autoimmunity has been mentioned in various possible pathogenetic mechanisms: premature ovarian aging with lower anti-Müllerian hormones, an increased risk of ovarian hyperstimulation, antiphospholipid antibody syndrome, cross-reactivity between anti-thyroid and anti-zona pellucida antibodies, endometriosis, genetic components, and systemic immune dysfunction with inhibition of immune tolerance [ 63 , 66 , 67 ]. A meta-analysis of four studies showed that among antibody-positive euthyroid women, the risk of unexplained infertility is increased (OR 1.5, 95% CI 1.1–2.0) [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is essential for the production of selenoproteins, which are crucial for the conversion of the thyroid hormone thyroxine (T4) into its active form, triiodothyronine (T3) [60,63]. The proper transformation of T4 to T3 is central for regulating metabolic rate and numerous cellular processes within the body [61,64,[107][108][109]. Proper thyroid function is crucial for a balanced hormonal environment in the female reproductive system [110].…”
Section: Seleniummentioning
confidence: 99%